2017
DOI: 10.1007/s40037-017-0389-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ownership of patient care: A dual-site qualitative study of faculty and residents from medicine and psychiatry

Abstract: IntroductionWith changes in duty hours and supervision requirements, educators have raised concerns about erosion of patient care ownership by resident physicians. However, the definition of ownership is unclear. This qualitative study investigated definitions of ownership in medicine and psychiatry faculty and residents.MethodsThe authors distributed an anonymous online survey regarding definitions of ownership to faculty and residents at the psychiatry and internal medicine residency programs at the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
1
25
1
Order By: Relevance
“…We developed items deductively based on the earlier work by Avey et al 12 Specifically, we adapted this scale to the constructs and themes identified in the studies by McLaren et al and Cowley et al 17,18 We constructed items with the goal of minimizing social desirability bias and the ceiling effect. 16 After developing a prototypic, 20-question ownership scale, we conducted cognitive interviews to assess the face validity of the scale items.…”
Section: Scale Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…We developed items deductively based on the earlier work by Avey et al 12 Specifically, we adapted this scale to the constructs and themes identified in the studies by McLaren et al and Cowley et al 17,18 We constructed items with the goal of minimizing social desirability bias and the ceiling effect. 16 After developing a prototypic, 20-question ownership scale, we conducted cognitive interviews to assess the face validity of the scale items.…”
Section: Scale Developmentmentioning
confidence: 99%
“…The first version of the ownership scale included items that measured all the constructs identified by Avey et al, 6 McLaren et al 17 , and Cowley et al 18 We made several modifications to the scale based on the cognitive interviews, which concluded after six interviews (four internal medicine residents and two attending physicians). Items were removed if there was no face validity or if ≥ 2 interviewees felt that the question was at high risk of social desirability bias or the ceiling effect.…”
Section: Cognitive Interviewingmentioning
confidence: 99%
See 3 more Smart Citations